Prioritization Of Enhancing Environmental Road Infrastructure In Slum Residential Zones - M.Arma Muslimin; Heni Fitriani; Febrian Hadinata (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Islam Lamongan, 2025)
This research was conducted using the AHP method to determine how to prioritize the handling of environmental roads in Pemulutan District, Ogan Ilir Regency. This research aims to prioritize the villages for environmental road handling in Pemulutan District, Ogan Ilir Regency. We employ a quantitative research approach, collecting data based on the established criteria. The data used includes secondary data and primary data. The stages of the research conducted include problem identification, followed by location determination, literature study, criteria determination and questionnaire design, data collection, data analysis using the Expert Choice application, and conclusion making. The research results show that among the several criteria established, the criteria of environmental road condition have 26,6% in determining the priority for environmental road improvements in the slum areas of the Pemulutan sub-district. We have identified Ibul Besar II Village as the village with the highest priority.